2021
DOI: 10.1016/j.paid.2021.110675
|View full text |Cite
|
Sign up to set email alerts
|

Seeking control during uncontrollable times: Control abilities and religiosity predict stress during COVID-19

Abstract: The COVID-19 pandemic has created an urgent need to understand the protective factors that can buffer individuals against psychological distress. We employed a latent-variable approach to examine how controlrelated factors such as religiosity, self-control, cognitive control, and health locus of control can act as resilience resources during stressful periods. We found that cognitive control emerged as a protective factor against COVID-19-related stress, whereas religiosity predicted a heightened level of stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…During the COVID-19 pandemic, several studies found that religiosity helped people to deal with stressful life events [ 18 , 19 , 20 , 21 , 22 ]. In contrast, other studies have not found significant associations between religiosity and mental health outcomes [ 23 , 24 ] or have found religiosity to be a small but significant predictor of higher stress levels during the COVID-19 pandemic [ 25 , 26 ]. Early meta-analyses reported small-to-moderate positive relationships between religiosity and mental health [ 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…During the COVID-19 pandemic, several studies found that religiosity helped people to deal with stressful life events [ 18 , 19 , 20 , 21 , 22 ]. In contrast, other studies have not found significant associations between religiosity and mental health outcomes [ 23 , 24 ] or have found religiosity to be a small but significant predictor of higher stress levels during the COVID-19 pandemic [ 25 , 26 ]. Early meta-analyses reported small-to-moderate positive relationships between religiosity and mental health [ 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 90%
“…Considering the relationship between religiosity and mental health issues [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] and trust in institutions [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ] during the COVID-19 pandemic, we expected that these variables would be predictors of change in fear of COVID-19 over a three-month period during the change in the pandemic situation. The number of total vaccinations visibly increased while the stringency of restrictions and mortality rate due to COVID-19 decreased over the three months in each country [ 50 , 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pandemic has also affected marital life, and numerous studies have reported domestic violence issues globally ( Abbas et al., 2020 ; Piquero et al., 2021 ; Gulati and Kelly, 2020 ; Noman et al., 2021 ). Religiosity levels among people have helped to maintain marital satisfaction ( Aman et al., 2019 ; Khoo et al., 2021 ). The coronavirus infection disease is dangerous to elderly diabetic patients ( Moradi et al., 2020 ).…”
Section: Social Stigma In the Covid-19 Pandemic And Mental Health Issuesmentioning
confidence: 99%
“…2021 ; Nee 2021 ), which was considered to be an important factor affecting delay discounting ( Kim et al. 2012 ; Steinbeis and Crone 2016 ) and was found as an important factor affecting COVID-19-related stress ( Khoo et al. 2021 ) and anxiety ( Demlrtas 2021 ).…”
Section: Discussionmentioning
confidence: 99%